A convenient synthesis of γ-functionalized cyclopentenones - Lahmar, Nour; Ayed, Taïcir Ben; Bellassoued, Moncef; Amri, Hassen (Beilstein Journal of Organic Chemistry, 2005)
The synthesis of γ-functionalized cyclopentenones was carried out in a few steps, starting firstly with the preparation of nitroketonic intermediates 2, which were readily transformed into 1,4-diketones using the Nef conversion. The intramolecular cyclization of the γ-diketones 3 in a basic medium, led to the functionalized cyclopentenones 4.
Keywords: Nef reaction; conjugated addition; nitroalkanes; 1,4-diketones; functionalized cyclopentenones